INTELLECTUAL RELIGIOSITY OF ISLAMIC BOARDING SCHOOL IN A. MUSTOFA BISRIâ€™S POETRY - Abdul Wachid B.S.; Herman J. Waluyo; Rachmat Djoko Pradopo; Suyitno Suyitno (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
This paper seeks to uncover A. Mustofa Bisri as a literary writer who â€œdeparts from Islamic boarding schoolâ€ which conveys intellectual religiosity through poetry. The concept of thinking used in this paper by exposing poetry as text, the world of Islamic boarding school as a con- text, and the interrelations both in poetry and religious Islamic intellectu- als as contextualization. First, the intensity of the written poetry is based on the intellectualreligiosity in theIslamicboarding school, so it is reli- giously timeless, and beyond the limitations of language usage. Aspects of events, aspects of experience, and aspects of the view of life (weltan- schauung) unite in the particular language and culture. Secondly, the prin- ciple that the idiocencracy of religious poetry based on Islamic values in the form of a poetical language is important to mark oneâ€™s poet as the context of the poetical of A. Mustofa Bisri. It should be interpreted not only as a symptom of poetical language that breaks away from the mean- ing of poetry (the religious experience expressed and simultaneously dis- played in poetry), but also the dynamics interrelated between poets, po- ems, and cultural backgrounds that surround them. Third, the religious experience manifested in the language of poetry is the deepestform of religious intellectual abstraction, i.e., divined and cherished love. This condition is shaped by the crystallization of knowledge as an action in the deepest dimension of oneâ€™s humanity to voice inner perceptions. By loving God, people will love Godâ€™s creation, man and the universe, as he loves himself. By loving each other and the universe as Godâ€™s creation, a lover will treat himself as a person of faith and do good deeds, and remind each other to hold fast to the truth, and remind each other to be patient. The concept cannot be separated from the perspective of al-Qurâ€™an and al-Hadith.